Expression of cell adhesion molecules and prognosis in breast cancer. Issue 2 (22nd November 2012) - Saadatmand, S.; de Kruijf, E. M.; Sajet, A.; Dekker‐Ensink, N. G.; van Nes, J. G. H.; Putter, H.; Smit, V. T. H. B. M.; van de Velde, C. J. H.; Liefers, G. J.; Kuppen, P. J. K.
Abstract: Background: Cell adhesion molecules (CAMs) play an important role in the process of metastasis. The prognostic value of tumour expression of N‐cadherin, E‐cadherin, carcinoembryonic antigen (CEA) and epithelial CAM (Ep‐CAM) was evaluated in patients with breast cancer. Methods: A tissue microarray of the patient cohort was stained immunohistochemically for all markers and analysed by microscopy. Expression was classified into two categories, with the median score as cut‐off level. For CEA, the above‐median category was further subdivided in two subgroups based on staining intensity (low or high intensity). Results: The cohort consisted of 574 patients with breast cancer with a median follow‐up of 19 years. Below‐median expression of E‐cadherin ( P = 0·015), and above‐median expression of N‐cadherin ( P = 0·004), Ep‐CAM ( P = 0·046) and CEA ( P = 0·001) all resulted in a shorter relapse‐free period. Multivariable analysis revealed E‐cadherin and CEA to be independent prognostic variables. Combined analysis of CEA and E‐cadherin expression showed a 3·6 times higher risk of relapse for patients with high‐intensity expression of CEA, regardless of E‐cadherin expression, compared with patients with below‐median CEA and above‐median E‐cadherin tumour expression (hazard ratio 3·60, 95 per cent confidence interval 2·12 to 6·11; P < 0·001). An interaction was found between expression of these two CAMs ( P < 0·001), suggesting a biological association. Conclusion: Combining E‐cadherin and CEA tumour expression provides a prognostic parameter with high discriminative power that is a candidate tool for prediction of prognosis in breast cancer. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd. Abstract : New prognostic markers